In vitro activity of aztreonam–avibactam against metallo-β-lactamase-producing Enterobacteriaceae—A multicenter study in China. (August 2020) - Zhang, Biying; Zhu, Zhichen; Jia, Wei; Qu, Fen; Huang, Bin; Shan, Bin; Yu, Hua; Tang, Yiwei; Chen, Liang; Du, Hong
Highlights: A total of 161 metallo-β-lactamase (MBL)-producing Enterobacteriaceae isolates were investigated for their in vitro sensitivity to aztreonam–avibactam. Klebsiella pneumoniae ( n = 73, 45.4%) and Escherichia coli ( n = 53, 32.9%) were the most common species. Pre-existing lung disease was associated with a hazard effect on worse disease outcomes among the patients with MBL- Enterobacteriaceae infections. The resistance rate of aztreonam in these isolates was as high as 81.4%, and the MIC90 of aztreonam–avibactam after adding avibactam was 1/4 μg/ml. The results suggest that the combination of aztreonam–avibactam is highly potent against MBL-producing Enterobacteriaceae in China. Abstract: Objectives: To study the molecular epidemiology of clinical metallo-β-lactamase (MBL)-producing Enterobacteriaceae isolates in China and to evaluate the antimicrobial susceptibility of MBL- Enterobacteriaceae isolates to aztreonam–avibactam. Methods: Bacterial speciation was determined using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. PCR was used to screen for common carbapenemase genes. Antimicrobial susceptibility testing of common clinical antibiotics and aztreonam–avibactam was performed using the standard broth microdilution method. Results: A total of 161 MBL- Enterobacteriaceae isolates were included, with Klebsiella pneumoniae ( n = 73, 45.4%) and Escherichia coli ( n = 53, 32.9%) being the most common species. Among the 161 isolates, bla NDM ( n = 151), bla IMP ( n = 13), and bla VIM ( n = 2) were detected, including five strains (3.1%) co-harboring two MBLs. MBL- Enterobacteriaceae isolates frequently contained two ( n = 55, 34.2%) or more ( n = 89, 55.3%) additional serine β-lactamase genes ( bla KPC, bla CTX-M, bla TEM, or bla SHV ). Antimicrobial susceptibility testing showed that 81.4% of isolates ( n = 131) were resistant to aztreonam. The rates of resistance to cefazolin, ceftazidime, ceftriaxone, cefotaxime, ampicillin–sulbactam, amoxicillin–clavulanic acid, and piperacillin–tazobactam were all over 90%. The addition of avibactam (4 μg/ml) significantly reduced the minimum inhibitory concentrations (MICs) of the aztreonam-resistant isolates by more than 8-fold (range ≤0.125 to 4 μg/ml), with a MIC50 /MIC90 of ≤0.125/1 μg/ml among the 131 isolates. Overall, 96.9% ( n = 156) of the total isolates were inhibited at an aztreonam–avibactam concentration of ≤1 μg/ml. Univariate and multivariate logistic regression analysis found that in patients with MBL- Enterobacteriaceae infections, the presence of pre-existing lung disease (adjusted odds ratio 8.267, 95% confidence interval 1.925–28.297; p = 0.004) was associated with a hazard effect on worse disease outcomes. Conclusions: The combined use of aztreonam–avibactam is highly potent against MBL- Enterobacteriaceae and may serve as a new candidate for the treatment of infections caused by MBL- Enterobacteriaceae in China.